Shuffle Lit!: Using iPod shuffles to encourage literacy experiences at home - Ashlee B Hover (Networks: An Online Journal for Teacher Research, 2018)
A kindergarten teacher used action research to examine how literature, audio books, homework, and Apple iPod Shuffles can be combined to encourage and improve literacy at home. The research participants consisted of 16 kindergarten students in Middle Tennessee and their parents. The kindergarten students took home a tote bag with the following contents: an Apple iPod Shuffle loaded with many audio stories, six books, two types of headphones, and an iPod listening/reading log. The students took the project materials home for a week to enjoy with their parents and other family members. The parents or siblings recorded the students’ experiences and other project related data through iPod logs and parent surveys. The kindergarten teacher/researcher recorded the students’ experiences and other project related data through student informal interviews. The results indicated that teachers, parents, and other family members who work together can utilize iPods to improve literacy at home. Teachers and parents can use this research to support and implement educational techniques that allow students to utilize iPods to learn more effectively.
Keywords: literacy; action research; kindergarten; technology; early childhood